Предмет: Математика,
автор: grisha6633
(6x+1)-(3-2x)=14 с проверкой
Ответы
Автор ответа:
18
(6х+1)-(3-2х)=14
6х+1-3-2х=14.
прибавляем 6х+2х и ещё 1-3
8х-2=14
8х=14+2
8х=16
х=16 : 8
х= 2
проверяем:
(6*2+1)-(3-2*2)=14
(12+1)-(3-4)=14
13-(-1)=14
14=14
grisha6633:
спасибо большое
Похожие вопросы
Предмет: Английский язык,
автор: viatcheslatt2009
Предмет: Физика,
автор: ustinova5ann2008
Предмет: Обществознание,
автор: tanya19792008
Предмет: Алгебра,
автор: ilia0702
Предмет: Алгебра,
автор: vipslavik19018